Post-communist states in the world community : selected papers from the Fifth World Congress of Central and East-European Studies - Kanet, Roger E.; Ferry, William E., editor (Hampshire : Macmillan Press, 1998)
World Congress of Central and East European Studies. th. 1995, Warsaw, Poland
Keywords: Europe, Eastern -- Economic policy-1989- -- Congresses; Europe, Eastern -- Politics and government -- 1989- -- Congresses; National security -- Europe, Eastern -- Congresses; Russia (Federation) -- Foreign relations -- Congresses